Left-to-right inverted single-lung transplantation: a case report - Runlei Hu; Jun Chen; Zhoubin Li; Yanni Chen; Weili Han (Journal of Cardiothoracic Surgery)
Abstract Background Lung transplantation is the most effective treatment for end-stage lung disease. However, the shortage of donor lungs is a major limitation. Inverted lung transplantation has the potential to expand the donor pool and make suitable donor lungs available to more patients. Case presentation We present the case of a 65-year-old male who developed interstitial lung disease and pulmonary fibrosis. After a comprehensive evaluation, it was determined that the patient met the criteria for a lung transplantation. The patient’s right lung condition was more severe than the left. Based on the allocation system, a suitable left donor lung was assigned to the patient. The patient underwent a left-to-right inverted single-lung transplantation. The transplanted lung gradually regained function postoperatively. Unfortunately, the patient passed away due to multiple organ failure caused by infection two months later. Conclusions In this report, we present a case of left-to-right inverted single-lung transplantation. Based on the preoperative evaluation and the patient’s consent, this surgical approach is feasible. This technique has the potential to broaden the pool of compatible donors and increase the number of recipients.